1990
DOI: 10.2307/1937606
|View full text |Cite
|
Sign up to set email alerts
|

Decay Rates, Nitrogen Fluxes, and Decomposer Communiies of Single‐ and Mixed‐Species Foliar Litter

Abstract: Decomposition rates, N fluxes, and abundances of decomposer organisms were quantified in mixed—species litterbags (containing leaves of two or three of the following tree species: Acer rubrum, Cornus florida, and Quercus prinus) and in litterbags containing leaves of a single species. Data from single—species litterbags were used to generate predicted decay rates, N fluxes, and abundances of decomposer organisms for mixed—species litterbags, against which observed values could be compared to determine if signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
193
7
6

Year Published

2001
2001
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(217 citation statements)
references
References 33 publications
11
193
7
6
Order By: Relevance
“…However, the low explanatory power of the fitted model suggests that other factors, such as output processes from the forest floor, can be important to explain C distribution in forest soils. On a given site, litter quality and its interaction with site properties are generally considered as the main factors controlling early phases of decomposition in forest ecosystems (Augusto et al 2015;Blair et al 1990). Our results provide consistent evidence of the importance of the conifer litterfall mass on the buildup of forest floor humus in forest soils (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the low explanatory power of the fitted model suggests that other factors, such as output processes from the forest floor, can be important to explain C distribution in forest soils. On a given site, litter quality and its interaction with site properties are generally considered as the main factors controlling early phases of decomposition in forest ecosystems (Augusto et al 2015;Blair et al 1990). Our results provide consistent evidence of the importance of the conifer litterfall mass on the buildup of forest floor humus in forest soils (Figs.…”
Section: Discussionmentioning
confidence: 99%
“…plant N uptake) of vascular plants in diverse communities. Decreased N release during decomposition seems unlikely because several studies on the relationship between plant diversity and organic matter turnover reported no or a positive e ect of plant diversity on N release (e.g., Blair et al 1990;Wardle et al 1997;Fornara et al 2009;Rosenkranz et al 2012). Lower dissolved N uxes in more diverse forests could instead have resulted from increased N demand of the vegetation as related to the greater productivity of more diverse forests (Morin et al 2011;Paquette and Messier 2011;Brassard et al 2013).…”
Section: Functional Relationship Between Plants and Dissolved N Uxesmentioning
confidence: 99%
“…Some studies have shown a relationship between biodiversity and nutrient availability (Hooper and Vitousek 1998;Symstad et al 1998;Tilman et al 1996Tilman et al , 1997 and mineralization (Hooper and Vitousek 1998). However, litter decomposition studies have not shown consistent effects of plant species diversity on decomposition rates (Blair et al 1990;Elliott et al 1993;Fyles and Fyles 1993;Hart et al 1993;Klemmedson 1991;Knops et al 1996;Kochy and Wilson 1997;Taylor et al 1989;Williams and Alexander 1991). Four recent studies have specifically examined the effect of litter diversity on decomposition (Bardgett and Shine 1999;Finzi and Canham 1998;Hector et al 2000;Wardle et al 1997).…”
Section: Introductionmentioning
confidence: 99%